A influência da lógica financeira no Prêmio Nacional da Qualidade - Fantti, Marina Borges Lima (Universidade Federal de São Carlos, 2017)
The financialization process made the shareholder value ideology become the main guiding principle of corporate behavior, which resulted in several changes in the organizations, for instance, in the profile and way the managers operates and in the strategies and management practices adopted. In this context, the approaches of quality management, which focus on providing superior value to the customers, had to adapt to maintain its legitimacy towards the shareholder value ideology. In this sense, this thesis aims to explore the influence of the elements of the management based on the financial logic in the National Quality Award, which is one of the most contemporary approaches of the quality management. The relevance of this study, due to the fact that there is a few empirical studies that analyzed the influence of financial logic in quality management approaches and in Brazilian organizations. In order to reach the described objective, an exploratory study was carried out based on secondary data, from a documentary research. This included the analysis of the existence of elements of the management based on the financial logic in the versions of the Management Excellence Model used by the National Quality Award and in the 66 companies that won the award between 1992 to 2016. The results point out the influence of financial logic in the National Quality Award. The analysis of the versions of the Management Excellence Model demonstrated that concepts of financial logic were gradually being incorporated instead of practices related to the quality management. The analysis of the profile of the companies that won the National Quality Award showed that 36% of the companies were awarded post-privatizations, which ocourred in the 1990s, with the predominance of companies of eletric energy segment. The analysis of the executives showed that members of the top management of more than 20 winning companies have acted on the boards of the National Quality Foudantion contributing to the formulation of the award guidelines. In addition, it was verified the existence of board interlockings in the winning organizations, which favored the dissemination of the Management Excellence Model and the National Quality Award. Finally, the analysis of the profile of the presidents of the winning companies demonstrated the predominance of executives with professional background in financial areas and post-graduation in finance, which are valued by the finance conception of control. This thesis indicated the reconversion of the the National Quality Award towards adherence to the management discourse based on the financial logic due to the need to maintain its legitimacy.
Keywords: Financeirização; Lógica financeira; Modelo de excelência da gestão; Prêmio Nacional da Qualidade; Financialization; Financial logic; Management excellence model; National Quality Award; Board interlocking; ENGENHARIAS::ENGENHARIA DE PRODUCAO